2017
DOI: 10.1111/jrh.12283
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Success of Participants Residing in Rural and Urban Areas

Abstract: Purpose Rural residents are significantly more likely to be overweight and obese than are urban residents. However, few data have compared weight control program responses in these population groups. Therefore, the primary aim of this study was to evaluate the weight loss outcomes of participants in a multi-site, on-line behavioral intervention by residential location (rural vs. urban) and, secondly, assess any possible differences in adherence to treatment goals. Methods 492 adult participants (Mean BMI = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…study participants 14 . Of note, there are important differences in the PA components of these interventions, with one providing no fitness center access, 13 another emphasizing built environment supports (e.g., use of local fitness centers and walking for transportation), 14 and the present study providing fitness center access over 12–18 months, with little emphasis on use of built environment to facilitate weight loss efforts. However, results only represent findings from three interventions.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…study participants 14 . Of note, there are important differences in the PA components of these interventions, with one providing no fitness center access, 13 another emphasizing built environment supports (e.g., use of local fitness centers and walking for transportation), 14 and the present study providing fitness center access over 12–18 months, with little emphasis on use of built environment to facilitate weight loss efforts. However, results only represent findings from three interventions.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, Mench et al. found that urbanicity did not moderate weight change during a 6‐month behavioral weight loss intervention 13 . In addition, Zenk et al.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations